2017
DOI: 10.1007/s00438-017-1351-z
|View full text |Cite
|
Sign up to set email alerts
|

PMK-1 p38 MAPK promotes cadmium stress resistance, the expression of SKN-1/Nrf and DAF-16 target genes, and protein biosynthesis in Caenorhabditis elegans

Abstract: The mechanisms of cadmium (Cd) resistance are complex and not sufficiently understood. The present study, therefore, aimed at assessing the roles of important components of stress-signaling pathways and of ABC transporters under severe Cd stress in Caenorhabditis elegans. Survival assays on mutant and control animals revealed a significant promotion of Cd resistance by the PMK-1 p38 MAP kinase, the transcription factor DAF-16/FoxO, and the ABC transporter MRP-1. Transcriptome profiling by RNA-Seq on wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…The results in kgb-1 Δ and pmk-1 Δ indicate a higher cadmium sensitivity of pmk-1 Δ. This finding is in accordance with previous results [24], which showed that PMK-1 signaling strongly promotes the cadmium resistance of C. elegans mostly via SKN-1 and DAF-16 target gene expression. Thus, while the cadmium resistance of pmk-1 Δ is impaired by the reduction in DAF-16 target gene expression, there were no specific effects of KGB-1 signaling on DAF-16 activity under hyperosmotic stress [44].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results in kgb-1 Δ and pmk-1 Δ indicate a higher cadmium sensitivity of pmk-1 Δ. This finding is in accordance with previous results [24], which showed that PMK-1 signaling strongly promotes the cadmium resistance of C. elegans mostly via SKN-1 and DAF-16 target gene expression. Thus, while the cadmium resistance of pmk-1 Δ is impaired by the reduction in DAF-16 target gene expression, there were no specific effects of KGB-1 signaling on DAF-16 activity under hyperosmotic stress [44].…”
Section: Discussionsupporting
confidence: 92%
“…From the data on developmental speed at different cadmium concentrations (Fig. 1a–j), it is evident that a CdCl 2 concentration of 10 mmol/L represents a severe abiotic stress/stressor (see also [24]). With regard to a severe biotic stress/stressor, preliminary experiments in our laboratory suggested to use C. arvensicola as animal feed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Many candidate antimicrobial genes have been identified in the genome of C. elegans ; but the role of the signaling pathways in regulating these antimicrobial peptides in response to bacterial infection is yet to be fully elucidated ( 40 42 ). In the present study, four genes ( tir-1, nsy-1, sek-1 , and pmk-1 ) in the p38 MAPK pathway, two genes ( daf-16 and age-1 ) in the DAF/IGF pathway, six genes ( lys-7, spp-1, abf-2, clec-85 , and clec-60 , and abf-3 ) reported previously that encode antimicrobial peptides ( 27 ), and three other genes ( sod-3, dbl-1 , and skn-1 ) reported previously with a defense function ( 23 , 43 , 44 ) were initially examined for their possible involvement in the immune response of the wild-type nematode. All the tested genes except for tir-1, clec-60 , and skn-1 were upregulated significantly as the results of responding to ETEC infection (Figure 2 ).…”
Section: Discussionmentioning
confidence: 97%